Impact of Diet on Dental Erosion among Adolescents in Lahore - Muhammad Waqas Rashid, Aliya Ehsan, Sadia Afif, Zenab Sarfraz, Musbah Shaheen, Anam Tahir, Amina Tariq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study has planned to explore the dental erosion prevalence among adolescents and relationship of diet with dental erosion among them. Method: This survey based study was conducted in Lahore. Data was collected from government secondary schools of Lahore. After the approval of research study from institutional ethical review committee, data was collected from 150 students with an age ranged from 13 to 16 years from 5 schools after the permission of principals and parents of the students. Frequencies and percentages were calculated to report the prevalence of dental erosion among adolescents. Chi-square test was used to explore the relationship between diet and dental erosion. Results: Findings of chi-square revealed a significant difference between the most frequently preferred food and dental erosion among adolescents (X2=9.67, P=.000). Due to carbonated drinks, 26.67% students were having dental erosion. Dental erosion was found in 20% students who prefer artificial juices, 14.67% students preferred energy drinks, 4% students prefer tea, 2% students prefer coffee, 24.67% students prefer ketchup and 6.67% prefer processed foods. Conclusion: Dental erosion is 21.42% among school going adolescents with age between ranging from 13 years to 16 years with low socioeconomic status in Pakistan.